Decongestion discriminates risk for one‐year mortality in patients with improving renal function in acute heart failure. (15th April 2021) - Wettersten, Nicholas; Horiuchi, Yu; van Veldhuisen, Dirk J.; Ix, Joachim H.; Mueller, Christian; Filippatos, Gerasimos; Nowak, Richard; Hogan, Christopher; Kontos, Michael C.; Cannon, Chad M.; Müeller, Gerhard A.; Birkhahn, Robert; et al.
Abstract : Aims: Improving renal function (IRF) is paradoxically associated with worse outcomes in acute heart failure (AHF), but outcomes may differ based on response to decongestion. We explored if the relationship of IRF with mortality in hospitalized AHF patients differs based on successful decongestion. Methods and results: We evaluated 760 AHF patients from AKINESIS for the relationship between IRF, change in B‐type natriuretic peptide (BNP), and 1‐year mortality. IRF was defined as a ≥20% increase in estimated glomerular filtration rate (eGFR) relative to admission. Adequate decongestion was defined as a ≥40% decrease in last measured BNP relative to admission. IRF occurred in 22% of patients who had a mean age of 69 years, 58% were men, 72% were white, and median admission eGFR was 49 mL/min/1.73 m 2 . IRF patients had more severe heart failure reflected by lower admission eGFR, higher blood urea nitrogen, lower systolic blood pressure, lower sodium, and higher use of inotropes. IRF patients had higher 1‐year mortality (25%) than non‐IRF patients (15%) ( P < 0.01). However, this relationship differed by BNP trajectory ( P ‐interaction = 0.03). When stratified by BNP change, non‐IRF patients and IRF patients with decreasing BNP had lower 1‐year mortality than either non‐IRF and IRF patients without decreasing BNP. However, in multivariate analysis, IRF was not associated with mortality [adjusted hazard ratio (HR) 1.0, 95% confidence interval (CI) 0.7–1.5] while BNP was (adjusted HR 0.5, 95% CI 0.3–0.7). When IRF was evaluated as transiently occurring or persisting at discharge, again only BNP change was significantly associated with mortality. Conclusion: Improving renal function is associated with mortality in AHF but not independent of other variables and congestion status. Achieving adequate decongestion, as reflected by lower BNP, in AHF is more strongly associated with mortality than IRF. Abstract : Improving renal function during a hospitalization for acute heart failure was found to identify patients at high‐risk for one‐year mortality; however, this risk was attenuated when patients were appropriately decongested, as defined by a ≥40% decrease in BNP, and when other high‐risk clinical features were adjusted for.